The Implementation of Portfolio Assessment in the English Class at Junior High School - Bning Puspita Natin; Siti Sundari; Made Adi Andayani T. (EFL Education Journal, 2021)
This research was conducted by using the qualitative case study design to report the implementation of portfolio assessment by the English teacher of public junior high school in the Regency of Banyuwangi., especially the detailed procedures as well as the students’ portfolio. The participant of this research was the seventh-grade English teacher. The English teacher was selected as the research participant because the English teacher has implemented the portfolio assessment since the academic year of 2017/2018. The English teacher used the strategy which was based on the students’ conditions and their needs. The researcher interviewed the English teacher three times and documented the students’ portfolios. Then, the researcher applied the model of Creswell (2013) to analyze the data collected. The result of this research revealed that the English teacher implemented the portfolio assessment which was adapted the portfolio assessment proposed by Zainul (2001) and the students’ needs as well as their conditions. Keyword: Portfolio Assessment, Students’ needs and condition, Teacher’s Implementation,